2016
DOI: 10.1016/j.archger.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and mortality in older adults: A systematic review and meta-analysis

Abstract: Multimorbidity was associated with an increase in risk of death. Multimorbidity measurement standardization is needed to produce more comparable estimates. Adjusted analysis which includes potential confounders might contribute to better understanding of causal relationships between multimorbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
405
4
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(452 citation statements)
references
References 65 publications
21
405
4
22
Order By: Relevance
“…A recent meta-analysis showed a positive relationship between number of conditions and risk of death 9. These results contrast with our findings and with those of several other recent studies that reported a null or protective effect for number of conditions on mortality 20 21.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis showed a positive relationship between number of conditions and risk of death 9. These results contrast with our findings and with those of several other recent studies that reported a null or protective effect for number of conditions on mortality 20 21.…”
Section: Discussioncontrasting
confidence: 99%
“…A meta-analysis detected a positive association between the number of chronic conditions and risk of death 9. Studies that have evaluated multimorbidity patterns based on combinations of common conditions or factor analysis have found that health outcomes vary according to the patterns analysed 10.…”
Section: Introductionmentioning
confidence: 99%
“…Multimorbidity has important clinical implications for patient well-being and survivorship, and is associated with increased mortality 18 . It also has a substantial impact on healthcare utilization and health economics.…”
Section: Discussionmentioning
confidence: 99%
“…2 In older people this is associated with higher rates of physical health conditions, polypharmacy, adverse drug events, high treatment burden, and greater use of health services. In younger people and people from less affluent areas, multimorbidity is often due to a combination of physical and mental health conditions.…”
Section: Introductionmentioning
confidence: 99%